2017
DOI: 10.4055/cios.2017.9.4.480
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Angles of the Traction Table on Lumbar Spine Ligaments: A Finite Element Study

Abstract: BackgroundThe traction bed is a noninvasive device for treating lower back pain caused by herniated intervertebral discs. In this study, we investigated the impact of the traction bed on the lower back as a means of increasing the disc height and creating a gap between facet joints.MethodsComputed tomography (CT) images were obtained from a female volunteer and a three-dimensional (3D) model was created using software package MIMICs 17.0. Afterwards, the 3D model was analyzed in an analytical software (Abaqus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…Even in the absence of standard protocol, such forces are note applied routinely in clinical practice. 27,28 The absence of representation of the ligaments is not the only limit of this model. The skin is also not represented in AMS, and the device had to be attached to the skeleton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the absence of standard protocol, such forces are note applied routinely in clinical practice. 27,28 The absence of representation of the ligaments is not the only limit of this model. The skin is also not represented in AMS, and the device had to be attached to the skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the cadaver was sitting slightly leaning forward, which can induce a slight inversion of curvature (lower lordosis) and increase the stresses exerted on the front of the disc. 2729…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lumbar lordosis curve plays a pivotal role in maintaining sagittal balance. IVDs are closely related to various spinal diseases including low back pain (LBP) because they function as a shock absorber inside the spine and reduce friction between vertebral bodies [ 1 , 2 ]. The damage or degeneration of IVD can lead to the mechanical compression of the spinal nerve or chemical stimulation, consequently causing various symptoms such as LBP, osteoarthrosis, loss of cartilage, and osteophyte formation in the facet joints and may lead to the development of spinal stenosis or degenerative spondylolisthesis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The damage or degeneration of IVD can lead to the mechanical compression of the spinal nerve or chemical stimulation, consequently causing various symptoms such as LBP, osteoarthrosis, loss of cartilage, and osteophyte formation in the facet joints and may lead to the development of spinal stenosis or degenerative spondylolisthesis [ 3 ]. To solve spinal dysfunction and LBP, many treatment measures focused on improving and modifying IVD physiology have been gaining attention, and related studies are advancing rapidly [ 1 , 2 , 4 , 5 ]. Studies have reported that the lifetime prevalence of LBP is as high as 84% and known to cause massive individual and economic burdens in industrialized nations such as Korea [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traction is a procedure that applies to SCI patients to degrade existing pressure, in which a gap is formed between articular facets within the joint. As a result, the compression of the spinal neural root, and in turn, the risk of inflammation will be decreased [17].…”
Section: Introductionmentioning
confidence: 99%